Use of a Lab-Ordering Pathway to Improve Adherence to Endocrine Society (ES) Guidelines for Early AM Timing and Testosterone Assay Method for Establishing Testosterone Deficiency - Gammoh, Emily (J Endocr Soc, 2021)
Introduction: Primary care providers (PCPs) prescribe the bulk of testosterone replacement therapy (TRT) at our institution, but our data show they are less likely than endocrinologists (ENDOs) to follow ES Guidelines for diagnosis of hypogonadism, based on two unequivocally low early AM [T] levels by tandem mass spectrometry (LC/MS/MS, PCP:213/783[27%]; ENDO:104/164[63%];p<0.0001). Methods: A lab ordering pathway was promulgated to direct PCPs to order 8AM T based on whether it was for monitoring therapy or diagnosing hypogonadism. The former leads to an order for Total T by electrochemiluminescence immunoassay (ECLIA), whereas the latter presents a choice between “Initial (diagnostic)” T or “Confirmatory” T. Ordering an initial diagnostic T requires a symptom to be chosen from a list of Low Libido, Loss of Early Morning Erections (EME), Fatigue, Erectile Dysfunction, or Other. Low libido or EME loss leads to an order for 8AM total T by LCMSMS, with a pop up reminder to instruct the patient to present at 8AM. Choosing any other symptom triggers a warning of non-specific symptoms, and an option to order 8AM total T by ECLIA, with the same pop up warning regarding timing. Ordering a confirmatory T requires a low initial 8AM T. Objective: To compare adherence by PCPs to ES guidelines based on timing and assay method for diagnosis of hypogonadism in the 6 months before (PRE) and 6 months after (POST) the date the pathway was promulgated. Results: There were 678 PRE and 884 POST lab orders for a diagnostic T for suspected hypogonadism. Although, adherence to 8AM timing was similar before and after promulgation (PRE 362/678[53.4%]; POST 452/884[51.1%]), there was a significant increase in the use of the accurate assay LC/MS/MS (PRE 39/678 [5.7%]; POST 105/884[11.9%];p<0.001). The 6.3% increase in LC/MS/MS use was reflected in a proportionate 7.3% reduction in ECLIA use (PRE 323/678 [47.6%]; POST (347/884 [39.3%]). Of note, all 105 patients in the POST cohort had a specific symptom (Loss of libido/EME) to justify the LC/MS/MS assay, whereas there was no such justification in the 39 in the PRE cohort. Conclusions: Promulgating a lab ordering pathway induced more appropriate use of LC/MS/MS in patients with specific symptoms associated with a high pre-test probability of hypogonadism. Although encouraging, it remains to be determined whether the more appropriate use of LC/MS/MS assays impacted testosterone prescribing practice. On the other hand, the lab ordering pathway did not improve adherence to early AM timing, despite the inclusion of pop up reminders to instruct patients to report early for blood draw. It is unclear whether that is attributable to PCPs not following through with the reminders, or to patients not following instruction due to ignorance, non-compliance, or practical problems, such as transportation and/or wait times at the lab. The lack of adherence to early AM timing has major implications for TRT.